Identifying type 2 diabetes risk classification systems and recommendations for review of podiatric care in an Australian Aboriginal health clinic - Lauren Blatchford; Pam Morey; Ruth McConigley (Journal of Foot and Ankle Research, 2015)
Abstract Background There are several risk classification systems developed to facilitate diabetic foot assessments and prioritise diabetes patients for foot prevention services according to risk factors. Utilisation of both The University of Texas Diabetic Foot Risk Classification System (UTDFRCS) and The National Evidence‐Based Guideline on Prevention, Identification and Management of Foot Complications in Diabetes (Part of the Guidelines on Management of Type 2 Diabetes), allows guidance for the podiatrist in terms of review timeframes for future assessments and treatment. The aim of this clinical audit was to classify Aboriginal type 2 diabetes subjects' risk status according to UTDFRCS and identify if evidence based standards are being met for podiatry services at the Albury‐Wodonga Aboriginal Health Service in New South Wales, Australia. Methods A retrospective clinical audit over a twenty six month period was undertaken at the Albury‐Wodonga Aboriginal Health Service, New South Wales. This is a primary health care facility that started podiatry services in August 2011. The primary variables of interest were the UTDFRCS for each subject and whether those participants met or did not meet the National Evidence‐Based Guideline for review appointment timeframes. Other variables of interest include age, gender, duration of diabetes, occasions of visits and cancelled and failure to attend appointments to the podiatry service over the data collection period. Results There was excellent overall adherence (94 %) of this sample population (n = 729) to the National Evidence‐Based Guideline for podiatric review timeframes according to their risk status. Males were reported to be less likely to comply with the review timeframes compared to women. There was no association between risk status and age (OR = 1.04, p = 0.11), duration of diabetes (OR = 1.03, p = 0.71) or gender (OR = 0.77, p = 0.67). Conclusions Regular foot examinations aid in stratifying patients according to risk status, guiding podiatry interventions to reduce the likelihood of ulceration and amputation. This primary health care setting has achieved podiatric evidence based standards for Aboriginal people with type 2 diabetes, demonstrated by acceptable timeframes for review appointments.